Understanding of Elementary School Teacher Education Students against the Rules of Basketball - Muhammad Noer Fadlan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research was conducted to equip each student participant in doing sports, especially in the field of basketball, at this level the research conducted by researchers can be understood together that each student in carrying out basketball sports activities is fairly good, and it can be said that all students who were sampled in this research has a good understanding. The research method carried out by the researcher uses a descriptive approach, where the researcher pours out all the results and a series of research in order to answer the phenomena that occur in the field, so that researchers are easy to categorize the results of the research.